Bronchial artery pseudoaneurysm presenting with hemoptysis and hemothorax after pulmonary lobectomy: a case report and literature review - Wei-Hao Zhang; Cheng-Yan Jin; Xiao Qi; Guang-Xin Zhang (Journal of Cardiothoracic Surgery)
Abstract Background Bronchial artery pseudoaneurysm is a rare vascular disorder, and cases of bronchial pseudoaneurysms reported after lung surgery are even rarer. The number of reported cases is very limited due to the unclear pathogenesis, lack of diagnostic criteria and treatment guidelines, and nonspecific clinical manifestations. Case presentation The paper reports a case of a patient with primary lung adenocarcinoma who developed hemoptysis, chest and back pain, and right hemothorax after lobectomy. Due to the lack of experience in treatment, we suspected that the above symptoms were caused by postoperative broncho-vascular fistula. The second thoracotomy and bronchoscopy examination did not reveal any obvious hemorrhage or fistula, and a subsequent bronchial arteriography confirmed the presence of a pseudoaneurysm in the right main bronchial artery. Later, the patient underwent transcatheter bronchial artery embolization and was followed up for half of a year after the operation without experiencing any of the previously mentioned symptoms. Conclusions The case reports the successful cure of bronchial artery pseudoaneurysm after pulmonary lobectomy through bronchial artery embolization.